Budgets and the timing, intensity, and composition of interest group lobbying in the U.S. states - de Figueiredo, John M. (Frontiers in Political Science, 2024)
This paper examines state level lobbying data to determine how budgeting affects the timing, intensity and composition of lobbying expenditures. Using a database of all available lobbying expenditures in the U.S. states ranging up to 25 years, the paper shows interest group lobbying increases substantially during the budgeting process, and the budgeting process is unlike other issues lobbyists face. Spikes in lobbying during budgeting are driven primarily by business groups, and these business groups account for most of the changes on the margin in lobbying activity. Moreover, even groups relatively unaffected by budgets lobby more intensely during legislative budgeting, consistent with the “Christmas tree” effect of appropriations and budget bills.